Ecological differentiation, lack of hybrids involving diploids, and asymmetric gene flow between polyploids in narrow contact zones of Senecio carniolicus (syn. Jacobaea carniolica, Asteraceae). Issue 6 (22nd February 2015) - Hülber, Karl; Sonnleitner, Michaela; Suda, Jan; Krejčíková, Jana; Schönswetter, Peter; Schneeweiss, Gerald M.; Winkler, Manuela
Abstract Areas of immediate contact of different cytotypes offer a unique opportunity to study evolutionary dynamics within heteroploid species and to assess isolation mechanisms governing coexistence of cytotypes of different ploidy. The degree of reproductive isolation of cytotypes, that is, the frequency of heteroploid crosses and subsequent formation of viable and (partly) fertile hybrids, plays a crucial role for the long‐term integrity of lineages in contact zones. Here, we assessed fine‐scale distribution, spatial clustering, and ecological niches as well as patterns of gene flow in parental and hybrid cytotypes in zones of immediate contact of di‐, tetra‐, and hexaploid Senecio carniolicus (Asteraceae) in the Eastern Alps. Cytotypes were spatially separated also at the investigated microscale; the strongest spatial separation was observed for the fully interfertile tetra‐ and hexaploids. The three main cytotypes showed highly significant niche differences, which were, however, weaker than across their entire distribution ranges in the Eastern Alps. Individuals with intermediate ploidy levels were found neither in the diploid/tetraploid nor in the diploid/hexaploid contact zones indicating strong reproductive barriers. In contrast, pentaploid individuals were frequent in the tetraploid/hexaploid contact zone, albeit limited to a narrow strip in the immediate contact zone of their parental cytotypes. AFLP fingerprinting data revealed introgressive gene flow mediated by pentaploid hybrids from tetra‐ to hexaploid individuals, but not vice versa. The ecological niche of pentaploids differed significantly from that of tetraploids but not from hexaploids.